The Effect of Sowing Time and Plant Density on the Yield of MaizeHybrids - Molnár, Zsuzsa; Sarvari, Mihály (Acta Agraria Debreceniensis, 2005)
The crop technology of maize has two important elements, sowing time and plant density. In 2003 and 2004 we studied the effect of these two factors on the growth and production of maize in an experiment carried out near Hajdúböszörmény. The soil of the experimental plots was meadow soil. Weather in both years was differed greatly. 2003 was drought. Neither the distribution nor the quantity of the precipitation were suitable in the growing season for maize. This fact basically determined the results. In 2004, we could talk about a favorable and rainy season. The distribution and quantity of precipitation was suitable between April and September. The average temperature was also suitable for maize. Results of the sowing time experiment: In 2003, we tested seven hybrids at four sowing times. Hybrids in the early maturity group gave the highest yield at the later sowing time, while the hybrids of the long maturity group gave it at the earlier planting time. The yield of PR34B97, PR36N70, PR36M53 hybrids was the best at every planting time. The moisture loss of hybrids in the late maturity group was faster in the maturity season, but the seed moisture content was higher than the hybrids with early sowing time. The seed moisture content was very low due to the droughty year. In two hybrid cases, this value was higher than 20% only at the fourth sowing time. In 2004, we examined the yield and seed moisture content of nine hybrids. In the favorable crop year, the yield of every hybrid was the highest at the second and third sowing time. Yields of PR34H31 and PR38B85 hybrids were significant. The seed moisture content at harvest was higher than the previous year due to the rainy season. In the case of hybrids sown later, this value was higher by 30%. However, we noticed that this value was lower at the earlier sowing time than at the later. The crop year had a more dynamic effect on maize than the sowing time. First of all, the quantity and distribution of precipitation played an important role in respect to yield safety. Results of the plant density experiment: We tested the reaction of hybrids at four plant densities (45,000, 60,000, 75,000 and 90,000 stock/ha) every two years. In 2003, the tested seven hybrids reached the highest yield at the 90,000 stock/ha in the face of a droughty year. The effect of forecrop and favorable nutrients caused these results. In the rainy 2004 year, the yield grew linear with the growing plant density. The yield of the best hybrids were 14-15 t/ha at the 90,000 stock/ha. Such a high plant density (90,000 stock/ha) couldn’t adaptable in farm conditions in rainy season. It is practical to determine the interval of plant density besides the optimum plant density of hybrids which gave correct yield. The farmers have to use the low value of this interval due to the frequent of the droughty years.